BEHAVIORAL APPROACH ON PUBLIC SECTOR MANAGEMENT - ALISA TRI NAWARINI (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
The concept of public administration evolved along with the increasing demands of improving public services, especially the quality of public employees. This condition requires a behavioral approach in managing the motivation of public employees who are able to encourage job satisfaction and extra-role behavior. However, research on the concept of public sector motivation (PSM) on the attitudes and behavior of public employees provides inconsistent results. This study aims to examine the effect of PSM on job satisfaction and organizational citizenship behavior (OCB) on public sector’s employees in Central Java. Using survey-based quantitative analysis, this study provides empirical evidence about the effect of PSM on job satisfaction and OCB. The findings of this study contribute to the public administration literature by providing guidance in encouraging employees behavior and positive behavior in the context of public organizations.